Make it in America : - Liveris, Andrew (Wiley, 2012)
America used to define itself by the things it built. We designed and produced the world's most important innovations, and in doing so, created a vibrant manufacturing sector that built the middle class. We manufactured our way to the top and became the undisputed economic leader among all nations. But over the last several decades, and especially in the last ten years, the sector that was America's great pride has eroded, costing millions of jobs and putting our long-term prosperity at risk. Now, as we struggle to recover from the worst recession in generations, our only chance to turn things around is to revive the American manufacturing sector--and to revolutionize it.